2018
DOI: 10.3389/fimmu.2018.03022
|View full text |Cite
|
Sign up to set email alerts
|

Fine Tuning the Cytokine Storm by IFN and IL-10 Following Neurotropic Coronavirus Encephalomyelitis

Abstract: The central nervous system (CNS) is vulnerable to several viral infections including herpes viruses, arboviruses and HIV to name a few. While a rapid and effective immune response is essential to limit viral spread and mortality, this anti-viral response needs to be tightly regulated in order to limit immune mediated tissue damage. This balance between effective virus control with limited pathology is especially important due to the highly specialized functions and limited regenerative capacity of neurons, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 78 publications
1
47
0
2
Order By: Relevance
“…A cytokine storm is also a key event causing death in patients infected with coronavirus 2,47 . Thus, inhibiting overactive immune responses is very important for preventing cytokine storms 48 . Indeed, we found that TAS2R10 may help prevent a cytokine storm because it can regulate natural killer cell‐mediated cytotoxicity, chemokine signaling pathways, T cell receptor signaling pathways, TNF signaling pathways, and others (Figure 3).…”
Section: Discussionmentioning
confidence: 88%
“…A cytokine storm is also a key event causing death in patients infected with coronavirus 2,47 . Thus, inhibiting overactive immune responses is very important for preventing cytokine storms 48 . Indeed, we found that TAS2R10 may help prevent a cytokine storm because it can regulate natural killer cell‐mediated cytotoxicity, chemokine signaling pathways, T cell receptor signaling pathways, TNF signaling pathways, and others (Figure 3).…”
Section: Discussionmentioning
confidence: 88%
“…Our results show that peripheral inflammation is mediated by a cytokine storm including persistent high levels of IL-12, TNF-α and IFN-, along with a pronounced splenomegaly, which thereof became a distinctive trait, and more important, a control of an efficient treatment. Accordingly, it has been previously shown that an increase in IL-10 correlates with a protective role mediated by this cytokine, limiting an exacerbated inflammation induced by pro-inflammatory cytokines such as IL-12 (26) and IFN- (39). Besides, TNF-α was associated with hepatic toxicity and diminished mice survival when IL-12 cDNA was injected alone (32).…”
Section: Discussionmentioning
confidence: 99%
“…Reports of neuromusculoskeletal disorders, complicating HCoV infections and COVID‐19, postulate that myopathies and neuropathies are a result of the significantly elevated inflammatory cytokines in patients' sera leading to virus‐induced immune damage 19,31,34 . This is further supported by evidence of immune‐mediated neurological conditions due to cytokine and chemokine release after HCoV infection as the disease progresses 21,24,44,45 . Another explanation could be the development of chronic illness myopathy (CIM), particularly in patients requiring mechanical ventilation for long periods 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Old age, underlying comorbidities, and critical illness are identified as risk factors that are capable of producing serious neurological manifestations in COVID‐19 patients 19 . HCoV infections, in more vulnerable patients, can induce an exacerbation of underlying neurological conditions via virus‐induced neuro‐immunopathology 14‐16,44,45 . It has been recognised that patients with pre‐existing neurological diseases, such as myasthenia gravis, 18 cerebrovascular stroke, 17,19,20 Parkinson's disease, 17,40,41 multiple sclerosis, 17,40,42 and other demyelinating disorders, 17,40,41 may be at a higher risk of contracting infection with SARS‐CoV‐2 or experiencing severe manifestations of COVID‐19.…”
Section: Discussionmentioning
confidence: 99%